Antifungal Activities Of Three Alkaloids From Ruta Angustifolia (L.) Pers. Against ATCC Susceptible Strains Of Candida Albicans And Candida Glabrata - Kamal, Laina Zarisa Mohd (2019)
The vital ability of medicinal plants to resist pathogenic microorganisms has led many scientists to isolate the active compounds and further investigate their mechanism of action. This is important as to fight the growing incidence of drugresistant pathogens. Overall, this study is focusing towards searching for new antifungal agent from alkaloids belong to Rutaceae family. The bioassay guided isolation was performed to isolate the antifungal active alkaloids. The impacts of these alkaloids on selected targeted genes have been experimented through quantitative real-time polymerase chain reaction (qRT-PCR). Leaves of the plant Ruta angustifolia (L.) Pers. was extracted and fractionated by using standard chromatographic techniques. Through bioassay-guided isolation, combined fraction of H3-3 and H4-8, fraction H10-9 and DA-10 yielded a total of three antifungal active alkaloids. These isolated alkaloids were then characterized and compared to the standard alkaloids by means of Thin Layer Chromatography (TLC) profile, melting point and maximum absorption of UV spectra in methanol (UVλ max- MeOH). The identification was further confirmed by HPLC spectroscopic data and was characterized as acridone, furoquinoline and 4-quinolone so named arborinine, skimmianine and graveoline respectively. The antifungal activites of the three alkaloids were tested against Candida albicans and Candida glabrata of ATCC strains with that of the standard antibiotics fluconazole. Broth microdilution assay of the alkaloids gave Minimum Inhibitory Concentration (MIC) values ranging from 250 μg/ml to 1000 μg/ml. Minimum Fungicidal Concentration (MFC) values were recorded at 500 μg/ml and 1000 μg/ml. The results from qRT-PCR analysis in C. albicans revealed that arborinine, skimmianine and graveoline down regulate all genes related to the central metabolism of Candida which are PCK, ICL and MLS. However, in the regulation of resistant genes, there is a decreased in ERG11, CDR2 and MDR after treated with arborinine, skimmianine and graveoline respectively. As in C. glabrata gene expression analysis, arborinine treated cells showed a significant decrease against three targeted genes namely ICL1, PCK1 and MLS1. Skimmianine and graveoline impact on the gene expression of the cell revealed the same impact when both of the compounds were able to down regulate ICL1 and PCK1 while MLS and ERG11 increased. The three isolated compounds were also able to reduce protein expression of Caicl1 in C. albicans through Western Blot. Overall, this study has proven that arborinine, skimmianine and graveoline can be remarkable component as antifungal agents with potential capacity to inhibit the growth and suppress the expression of the targeted genes and protein of C. albicans and C. glabrata.